Unveiling the Realities of Women's Empowerment in Jammu & Kashmir (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study explores the many aspects of women's empowerment in Jammu & Kashmir (J&K), going beyond simple words to provide a detailed comprehension of the difficulties, advancements, and intricacies experienced by women in the area. The article examines many aspects of women's empowerment activities in J&K, including socio-cultural norms, legal frameworks, economic possibilities, and political engagement. This study rigorously analyzes the influence of conflict, security dynamics, and social views on the ability of women to take action and make decisions. This paper seeks to provide a comprehensive analysis of women's empowerment in J&K by examining both achievements and ongoing obstacles. Its objective is to enhance the overall discussion on this topic and offer valuable insights to policymakers, practitioners, and advocates who are dedicated to achieving significant and enduring advancements in gender equality and women's rights.